SABU LANGUAGE PRESERVATION IN MATAWAI ATU VILLAGE, EAST SUMBA REGENCY, EAST NUSA TENGGARA - Putri, Angel Maharani Dewi; Utami, Sri; Mardiana, Ninik (Transpublika Publisher, 2022)
This research seeks to describe the Sabu community's attempts to preserve their indigenous language in Matawai Atu Village, as well as the elements that influence Sabu language preservation. This is a descriptive qualitative study. In this study, data was gathered by listening, interviewing, and recording procedures, as well as listening and speaking approaches in observation. The descriptive qualitative approach was utilized for data analysis, with stages of finishing the translating process, data reduction, data display, and drawing conclusions. Unstructured interviews, observations, and recording devices were employed as data gathering instruments. The time triangulation approach is utilized for data veracity. The study's findings indicate that the Sabu tribal community, which tries to maintain the use of their local language due to several factors such as (1) same-ethnic marriage and (2) using the Sabu language for daily conversation, plays a very important role in the survival of the Sabu language in Matawai Atu Village, East Sumba Regency, (3) the geographical concentration factor, and (4) the speaker loyalty factor.